The Scientific Article in the Age of Digitization - Owen, J. Mackenzie; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This book outlines the consequences of digitization for peer-reviewed research articles published in electronic journals. It has often been argued that digitization will revolutionize scientific communication. However, this study shows that this is not the case as far as scientific journals are concerned. Authors make little or no use of the possibilities offered by the digital medium, new procedures for electronic peer review have not replaced traditional peer review, and users do not seem to accept new forms of interaction offered by some electronic journals. The main innovations are to be found at the level of the infrastructures developed by publishers. Scientists themselves appear to be reluctant to change their established patterns of behaviour in formal scientific communication. The book provides a theoretical background to the history and structure of scientific communication, as well as an in-depth study of electronic journals over the period 1987-2004. It offers a unique approach that questions more conventional ideas about the 'revolutionary' impact of digitization on scientific communication and the innovative role of publishers and academia.
THE DEVELOPMENT OF SCIENTIFIC COMMUNICATION -- THE SCIENTIFIC COMMUNICATION SYSTEM -- THE DIGITIZATION OF INFORMATION RESOURCES -- THE ELECTRONIC JOURNAL 1987-2004 -- DIGITIZATION AND THE EVOLUTION OF SCIENTIFIC COMMUNICATION.
Keywords: HUMANITIES; INFORMATION SYSTEMS; LIBRARY SCIENCE; PUBLISHERS AND PUBLISHING; SOCIAL SCIENCES; HUMANITIES / ARTS; LIBRARY SCIENCE; INFORMATION SYSTEMS AND COMMUNICATION SERVICE; INFORMATION SYSTEMS APPLICATIONS (INCL.INTERNET).; SOCIAL SCIENCES, GENERAL; PRINTING AND PUBLISHING